Enforcing State Ethics: Quo Vadis Law on Ethics of State Officials - Kusuma, Lalu Aria Nata (Faculty of Law, University of Dr. Soetomo, 2023)
Various ethical violations committed by state officials today are very concerning. In fact, there has been a legal product in the form of MPR Decree No. VI/MPR/2001 concerning the Ethics of National Life (MPR Decree No. VI/MPR/2001) which should be used as a guiding star. Unfortunately, the existence of MPR Decree VI/MPR/2001 is almost forgotten and unaware of its existence. This research aims to examine the existence of MPR Decree VI/MPR/2001 and the idea of forming the Law on Ethics of State officials. The research method used is normative legal research, using a legislative approach and a conceptual approach. The results of the study show that the weak binding force of the MPR Decree as a legal product in the hierarchy of laws and regulations and the absence of an effective supervision and enforcement mechanism have implications for the neglect of the MPR Decree, which in this case includes the provisions regulated in the MPR Decree VI/MPR/2001. Reflecting on these conditions, it is necessary to regulate the issue of the ethics of state officials in a Law on Ethics of State officials to ensure the administration of the state based on moral and ethical values. The existence of the Law on Ethics of State officials will later regulate the code of ethics and code of conduct of state officials, as well as regulate an independent external ethics supervisory institution in the form of the State Officials Ethics Court.